How Randai Become A Medium for Information and Education to Prevent Stunting? A Case Study in West Sumatera Province - Nata, Lismomon; Barlian, Eri; ., Erianjoni; ., Indrayuda; Syah, Nurhasan (Journal of Ecohumanism, 2025)
Although the globalization has already affected the information about the human’s health, it is found still some people are careless to feed their families with good nutrition and it causes high number of stunting cases in Indonesia. Local wisdom, called randai, is considered as one of the solutions among the strategies used by the governments to minimize the case. This research aims to explore how randai becomes a medium for information and education to prevent stunting cases. It is expected that this research could inform and educate the society well about the importance food for body to grow strong, smart and healthy. It used a qualitative research by using case study design. Data were collected by observing and conducting discussion to the randai group performances from three differences areas in West Sumatera Province and it was collected by using observation checklist and interview guideline technique. Data were analyzed by using content analysis. The observed items on the randai group performances research were theme, action; characters; language; and costumes. The research shows that randai group performances have already communicated and educated the randai auidiences about the importance of the body to consume good food and responsibility of parents to children, which affects the growth, health and smartness, towards its theme, action; characters; language; and costumes. By communicating enough food for the body and parents control or responsibility on children health in randai performance, it could communicate and educate the society about the stunting prevention towards its visual information such as action, character, and costume and verbal information such as theme and language used.